Policy Evaluation of the Village-Owned Enterprise (BUMDes) Program in Improving the Village Economy - Muzani Syukur; Bambang Irawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to evaluate the policy implementation of the Village-Owned Enterprise (BUMDes) program in Bojong Village, Banjarwangi District, Garut Regency, in improving the village economy. The research employs a qualitative approach with a descriptive method and uses the CIPP (Context, Input, Process, Product) evaluation model to analyze the effectiveness of the program comprehensively. Data were collected through in-depth interviews, participatory observation, and documentation involving village officials, BUMDes managers, community members, and other stakeholders. The results indicate that, in the context aspect, the BUMDes program is relevant to the socio-economic conditions and needs of the community and is supported by a clear legal framework. However, the formulation of objectives and business development has not been fully based on a comprehensive analysis of local economic potential. In terms of input, the program is supported by organizational structures, village regulations, and initial capital from village funds, yet it still faces limitations in human resource capacity, infrastructure, and access to additional funding. From the process perspective, the implementation of BUMDes has generally followed established mechanisms and involved relevant village institutions. Nevertheless, community participation, socialization efforts, and internal monitoring and evaluation systems remain suboptimal. In the product aspect, the program has contributed to local economic activities and created initial business opportunities for the community. However, its impact on increasing village original revenue (PADes), employment, and overall community welfare is still limited and unevenly distributed. In conclusion, although the BUMDes policy in Bojong Village is conceptually appropriate, its effectiveness is constrained by weaknesses in input quality and implementation processes, which ultimately affect the overall outcomes of the program.